2020
DOI: 10.1371/journal.pbio.3000750
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitivity is an essential component of phototransduction in vertebrate rods

Abstract: Photoreceptors are specialized cells devoted to the transduction of the incoming visual signals. Rods are able also to shed from their tip old disks and to synthesize at the base of the outer segment (OS) new disks. By combining electrophysiology, optical tweezers (OTs), and biochemistry, we investigate mechanosensitivity in the rods of Xenopus laevis, and we show that 1) mechanosensitive channels (MSCs), transient receptor potential canonical 1 (TRPC1), and Piezo1 are present in rod inner segments (ISs); 2) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Past studies have shown that rods, under strong illumination, expand, or shrink in length by few micrometers (Hardie and Franze, 2012;Lu et al, 2018), which indicates the existence of mechanical machinery within rod cells. Using OT, Bocchero et al (2020) have therefore confirmed this hypothesis.…”
Section: Communication Modalities Of Neuronssupporting
confidence: 53%
“…Past studies have shown that rods, under strong illumination, expand, or shrink in length by few micrometers (Hardie and Franze, 2012;Lu et al, 2018), which indicates the existence of mechanical machinery within rod cells. Using OT, Bocchero et al (2020) have therefore confirmed this hypothesis.…”
Section: Communication Modalities Of Neuronssupporting
confidence: 53%
“…This study does not include all the MSCs found in the outer retina. The rod IS also expresses Piezo1 and TRP canonical 1 (TRPC1) [ 119 , 120 ]. Piezo1 in the dorsal root ganglion neurons mediates rapidly adapting mechanically induced cation currents, which reverse around 10 mV [ 121 , 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we note that recent work has shown that human cones ( 45 ) and vertebrate rod-photoreceptors ( 46 ) contract photomechanically, comparable to Drosophila photoreceptor microsaccades ( 3, 4 ). It will be interesting to see whether these microsaccades increase visual acuity and participate in stereo vision and whether high-intensity X-rays also activate them ( 8–10 ).…”
Section: Discussionmentioning
confidence: 63%